The developing human : clinically oriebted embryology - Moore, Keith L. (Saunders/Elsevier, 2013)
The Developing Human: Clinically Oriented Embryology, by Drs. Keith L. Moore, T.V.N. Persaud, and Mark G. Torchia, delivers the world's most complete, visually rich, and clinically oriented coverage of this complex subject. Written by some of the world's most famous anatomists, it presents week-by-week and stage-by-stage views of how fetal organs and systems develop, why and when birth defects occur, and what roles the placenta and fetal membranes play in development. You can also access the complete contents online at www.studentconsult.com, along with 17 remarkable animations, downloadable illustrations, additional review questions and answers, and more. Access the full contents of the book online at www.studentconsult.com - as well as 17 remarkable animations that bring normal and abnormal embryological development to life, downloadable images, and hundreds of additional review questions and answers to test your mastery of the material. Acquire a detailed grasp of human embryology with the world's most comprehensive, richly illustrated, and clinically oriented coverage from a cadre of leading world authorities. Effectively prepare for exams with review questions and answers at the end of each chapter.